Rotating helical turbulence: Three-dimensionalization or self-similarity in the small scales? - Pouquet, A. (2011)
We present numerical evidence on how three-dimensionalization is recovered at small scale in rotating turbulence with helical forcing provided by a Beltrami flow. The relevant ranges (large-scale inverse cascade of energy, anisotropic and isotropic direct cascades of energy and helicity, dissipative) are each moderately resolved. These results stem from large direct numerical simulations on grids of either 15363 or 30723 points. In the latter case, the scale at which the inertial wave time and the eddy turn-over time are equal is found to be more than one order of magnitude larger than the dissipation scale. We also examine how the presence of such an intermediate scale could affect truncation due to the use of a helical spectral Large Eddy Simulation procedure which can allow for extending the analysis to a wider range of parameters. Finally, the self-similarity of the direct cascade of energy to small scales for rotating flows, observed recently in numerical simulations as well as in several laboratory experiments, will be discussed briefly for its scaling properties and its conformal invariance.